On logic gates with complex numbers - AlMasri, M. W. (International journal of parallel, emergent and distributed systems, 2024)
Logic gates can be written in terms of complex differential operators, where the inputs and outputs are holomorphic functions with several variables. Using the polar representation of complex numbers, we arrive at an immediate connection between the oscillatory behavior of the system and logic gates. We discuss the universality of this formalism in a variety of computing systems.